Articaine and Dexmedetomidine – Supplemented Articaine for Arteriovenous Fistula Creation under Ultrasound-guided Supraclavicular Block - Armanious, Simon Halim (Anesth Essays Res, 2020)
BACKGROUND: Articaine has emerged as a local anesthetic (LA) that produces sensory and motor blockade shorter than bupivacaine and lower in neurotoxicity than lidocaine. Studies have shown that adding dexmedetomidine to LA produces prolongation of sensory and motor bock duration. Early regain of motor power with adequate analgesia is needed in hemodialysis fistula creation surgery, for early start of physiotherapy. We designed this study to test efficacy of adding dexmedetomidine to articaine on the duration of sensory and motor block. METHODS: After university review board approval, written informed consent to participate in the study was obtained. Patients with chronic renal failure undergoing radiocephalic hemodialysis fistula creation were eligible for enrollment in this double-blind, randomized trial. Patients receive either 40 ml of 2% articaine hydrochloride or 40 ml of articaine 2% mixed with dexmedetomidine (1 μg.kg (− 1)). Sensory block duration in minutes is assessed by pinprick test and motor block duration in minutes is tested by Bromage scale; both are recorded as a primary outcome. Secondary outcomes, including onset of sensory and motor block, time for rescue analgesia, hemodynamic changes, oversedation, and possible side effect, were recorded. RESULTS: Fifty patients were enrolled in the study (25 in the articaine Group A and 25 in the articaine and dexmedetomidine group [AD]). Longer sensory block duration was in Group AD (230–260 min) than in Group A (172–185 min) with P < 0.001. In addition, motor block duration was significantly longer in Group AD than in Group A, (220 ± 110 min), (165 ± 45 min), respectively. The duration of effective analgesia was significantly longer in Group AD (363 ± 134 min) versus in Group A (244 ± 84 min). The onset of block was short and similar between groups. CONCLUSION: Addition of dexmedetomidine to articaine during arteriovenous fistula creation provide prolongation of sensory and motor block duration and augment analgesia. TRIAL REGISTRATION: This trial was registered at Clinical trial.gov https://clinicaltrials.gov/ct2/show/NCT04171349 with the identification number NCT04171349.